Interaction of actors in the sectoral ict innovation system in Costa Rica - Quesada Rosales, Ariella (2017)
This paper identifies the actors involved in the sectoral ICT innovation system in Costa Rica and describes their interactions for three key activities: human resources training, R&D&I, and creation of new enterprises. We use a qualitative approach and consider five stages: literature review, conceptual delimitation for the ICT sectors in Costa Rica, identification of actors, and analysis of their interactions. The analysis showed coordination problems among actors in the industry, government and academic sectors for these three activities. New institutions are proposed to solve these problems and improve the coordination among actors.